Market infrastructure and economic development - Setty, H. Nagaraja (Bangalore, 2000)
In this book the relationship between agricultural productivity and market arrivals is analyzed in order to examine whether development of infrastructure has benefited market development, particularly in terms of increased market arrivals, better farmer participation and better returns to them.
Keywords: Economic development